2014
DOI: 10.3136/fstr.20.799
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a Novel Oligophosphopeptide with High Calcium Binding Activity from Carp Egg Hydrolysate

Abstract: Keywords: purification, carp eggs, hydrolysate, dephosphorization, calcium binding activity, oligophosphopeptide IntroductionThe global fishery production reached 178 million tons in 2011(i), more than 50% of which was discarded as inedible byproducts such as bone, skin, internal organs, head and eggs (Jung et al., 2005). Plentiful research have been implemented on utilizing fishery byproducts (Chakraborty et al., 2011;Duan et al., 2009;Kongsri et al., 2013;Mori et al., 2013). However, the utilization studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…It was shown that the <1 kDa fraction had the highest activity (277.96 mg Ca 2+ /g protein), which was lower than that of CPP about 1.7 folds. This finding was in agreement with those of Huang et al () and Huang et al () who reported that the lowest molecular weight peptide showed the highest calcium‐binding activity.…”
Section: Resultssupporting
confidence: 93%
“…It was shown that the <1 kDa fraction had the highest activity (277.96 mg Ca 2+ /g protein), which was lower than that of CPP about 1.7 folds. This finding was in agreement with those of Huang et al () and Huang et al () who reported that the lowest molecular weight peptide showed the highest calcium‐binding activity.…”
Section: Resultssupporting
confidence: 93%
“…7 However, numerous studies have focused on using organic supplements due to their increased bioavailability. 8−10 To this end, many organic supplements improve the absorptive ability of mineral elements and include oligophosphopeptide, 11 chicken eggshell matrix proteins, 12 tilapia protein hydrolysate, 13 whey protein hydrolysates, 14 hen egg yolk phosvitin, 15 and desalted duck egg white peptides. 16 Casein phosphopeptides (CPPs) are derived from trypsinmediated casein cleavage and are considered mineral carriers with potential roles in improving elemental mineral absorption.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As shown in Figure 3 (c), two major fractions (R1, R2) were separated through the semi-preparative C18 column. The calcium-binding activity of an oligophosphopeptide from carp egg hydrolysate and pollack backbone peptide were 5.0, 7.0, and 7.85 mmol/g-protein when the protein concentration was 50 mg/L [6,7, 28,35]. Compared with the peptides above, the peptide derived from bovine bone showed that R2 (BBP) had the highest calcium-binding activity of 8.25 mmol/g-protein.…”
Section: Isolation and Purification Of Calcium Binding Peptidesmentioning
confidence: 99%
“…H4 was eluted with the maximum concentration of phosphate buffer (150 mM) and exhibited the highest calcium-binding ability of 7.02 mmol/gprotein, which showed that HA chromatography was very effective in separating peptide with the calcium-binding activity. The oligophosphopeptides with calcium-binding activity have been successfully separated and obtained from fish bone and carp egg [7,28] using HA affinity chromatography.…”
Section: Isolation and Purification Of Calcium Binding Peptidesmentioning
confidence: 99%
See 1 more Smart Citation